Nutritional Strategies for Lowering Cholesterol in Foods and Lifestyles that Support Heart Health - Snema, Aduwera Akerele (PSPP JOURNALS, 2023)
This looks at investigates the difficult courting among technology usage and work-lifestyles stability in modern-day paintings environments. Through qualitative analysis, we explore how employees perceive and navigate the demanding situations posed by way of consistent connectivity and virtual integration. Findings display numerous strategies people hire to control work-existence obstacles, highlighting the effect of organizational tradition and leadership. Moreover, differential results of generation throughout demographic and occupational groups are observed, emphasizing the want for tailor-made interventions. Ethical implications of technology-enabled interventions also are discussed. Our observe contributes valuable insights to the information of labor-existence dynamics inside the digital age.